Pelatihan Pengenalan Aplikasi Editing Video Sebagai Sarana Dakwah di Youtube Bagi Pemuda/i Perumahan Pondok 6 - Hasibuan, Ade Zulkarnain; Munjiat Setiani Asih (Jurnal Pengabdian Masyarakat, 2022)
The PkM activity carried out in the Kolam Village, Pondok 6 Housing, aims to provide counseling to the youth of Pondok 6. So the use of technology is not only used in urban areas, but the long-term target of using technology is also to penetrate the villages. Where the technology used can increase knowledge and abilities in preaching and studying. The purpose of the counseling is to provide knowledge to young people to take advantage of YouTube support applications so that they have the ability to develop ways of broadcasting Islamic teachings on social media.